2005
DOI: 10.1186/1465-9921-6-56
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 induces human alveolar epithelial to mesenchymal cell transition (EMT)

Abstract: Background: Fibroblastic foci are characteristic features in lung parenchyma of patients with idiopathic pulmonary fibrosis (IPF). They comprise aggregates of mesenchymal cells which underlie sites of unresolved epithelial injury and are associated with progression of fibrosis. However, the cellular origins of these mesenchymal phenotypes remain unclear. We examined whether the potent fibrogenic cytokine TGF-β1 could induce epithelial mesenchymal transition (EMT) in the human alveolar epithelial cell line, A54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

67
537
5
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 664 publications
(612 citation statements)
references
References 52 publications
(65 reference statements)
67
537
5
3
Order By: Relevance
“…It is involved in a variety of normal physiological as well as pathological processes such as cancer progression and renal fibrosis (16,17). Recent evidence suggests a potential role for EMT in the pathogenesis of pulmonary fibrosis (14,15,(41)(42)(43). MFT is a similar process and has been described as a major factor in the development of peritoneal fibrosis (18).…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in a variety of normal physiological as well as pathological processes such as cancer progression and renal fibrosis (16,17). Recent evidence suggests a potential role for EMT in the pathogenesis of pulmonary fibrosis (14,15,(41)(42)(43). MFT is a similar process and has been described as a major factor in the development of peritoneal fibrosis (18).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that TGF-β1 protein overexpression is closely associated with lung cancer progression and metastasis. As we all know, TGF-β1 is one of growth factors that can regulate extracellular matrix composition and induces epithelial-to-mesenchymal transition (EMT) in alveolar epithelial cell (Kasai et al, 2005). During the EMT process, carcinoma cells lose cell-cell adherence junctions and transfer to fibroblast-like morphology, and become motile and invasive.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, recently, it was shown that lung epithelial cells undergo epithelial-mesenchymal transition (EMT) to become myofibroblasts after treatment with TGF-b 1 in vitro. 12,13 The EMT of lung epithelial cells also seems to be induced in the lungs of pulmonary fibrosis patients and bleomycin-treated animals. 12,14 Furthermore, inhibition of EMT by knockout of the integrin-a3 gene has been shown to suppress bleomycininduced pulmonary fibrosis in mice.…”
mentioning
confidence: 99%